Peran Kelompok Sadar Wisata Sidokumpul Kompak Berhias (SIKOBER) Dalam Pengembangan Pariwisata di Kampung Kreasi Kabupaten Gresik - Upik Dyah Eka Noviyanti; Amiera Rasyita Serinanda (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2022)
The purpose of this study was to describe the role of the supporting and inhibiting factors of the SIKOBER Tourism Awareness Group (Sidokumpul Kompak Berhias) in developing the Kreasi Village in Sidokumpul Village, Gresik Regency. Kreasi Village, which used to be a place known as a slum area, has now become a tourist attraction in the midst of the crowded city of Gresik. This study used a qualitative approach, namely data collection was carried out by interview, observation, and use of document materials which were then presented in descriptive form. The results of this study indicate that the SIKOBER Tourism Awareness Group has several roles in the development of this tourist village. The SIKOBER Tourism Awareness Group has conducted public education in the form of providing training on environmental hygiene, recycling waste management into goods of economic value, urban farming, and the establishment of the Creative Village Institute to develop tourism in the area. The community's increased capacity after the training and collaboration between the SIKOBER Tourism Awareness Group and PT Pertamina Lubricant is a supporting factor in the successful development of the Kreasi village. Meanwhile, the inhibiting factors in tourism development in Kreasi Village are the lack of funding sources and the lack of community participation in the development of this Kreasi Village